Dynamics of Mercury Pollution on Regional and Global Scales Atmospheric Processes and Human Exposures Around the World - Pirrone, Nicola; Mahaffey, Kathryn R. (Springer US : Imprint: Springer, 2005)
Mercury pollution in different regions of the world is a growing concern from an environmental and epidemiological point of view. The increasing trends of energy production from fossil fuel combustion, mercury usage in a large variety of goods and products, and the lack of emission control policy, especially in fast developing countries, represent a major environmental and political issue for national and international organisations and governments as well. In the last decade, there has been a significant effort to improve our knowledge on different aspects involved in the biogeochemical cycle of mercury in the environment and its impact on human health. Special attention has been devoted to fill the gaps in our knowledge on physical and chemical processes involved in the transfer of mercury compounds released to the atmosphere from natural and anthropogenic sources to terrestrial and aquatic receptors. Significant progress was made on assessing the spatial and temporal distributions of atmospheric mercury and its depositional fluxes. Dynamics of Mercury Pollution on Regional and Global Scales: Atmospheric Processes and Human Exposures Around the World provides a detailed overview of our current understanding of different dynamic patterns involved in the redistribution of mercury in the global environment, and its impact on human health and ecosystems.